Constitutional Guarantees of the Right to Privacy of Personal Data of Citizens in the Era of Government Digitalization - Rahmawati, Aprilia Dwi; Wardana, Dodi Jaya (Journal of Law, Politic and Humanities, 2025)
The advancement of digital technology and the transformation toward electronic- based governance have brought new challenges to the protection of citizens' privacy rights, particularly concerning personal data. In the digital era, personal data has become increasingly vulnerable to misuse and databreaches, while Indonesia’s legal framework is still in the process of adapting to these issues. This study aims to analyze the extent to which the right to privacy and personal data is constitutionallyprotected, and how the state is obligated to ensure such protection. This research uses normative legal methods with a juridical- conceptual approach. The findings indicate that the right to privacy is constitutionally guaranteed in the 1945 Constitution of the Republic of Indonesia, particularly in Article 28G paragraph (1) and Article 28H paragraph (4), although personal data is not explicitly mentioned. The enactment of Law No. 27 of 2022 on Personal Data Protection marks a significant step in strengthening legal safeguards for digital privacy. It must be supported by the establishment of an independent supervisory authority, adaptive policy formulation, and increased digital literacy among the public.